2021
DOI: 10.48550/arxiv.2111.01600
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Milliarcsecond localisation of the repeating FRB 20201124A

K. Nimmo,
D. M. Hewitt,
J. W. T. Hessels
et al.

Abstract: Very long baseline interferometric (VLBI) localisations of repeating fast radio bursts (FRBs) have demonstrated a diversity of local environments: from nearby star-forming regions to globular clusters. Here we report the VLBI localisation of FRB 20201124A using an ad-hoc array of dishes that also participate in the European VLBI Network (EVN). In our campaign, we detected 18 total bursts from FRB 20201124A at two separate epochs. By combining the visibilities from both observing epochs, we were able to localis… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…We followed up FRB 20201124A within the PRECISE project during different epochs and, we detected 13 and 5 bursts in two of them [30]. By combining the data from all these bursts, we were able to localize FRB 20201124A with a 1-𝜎 uncertainty of 2.7 milliarcseconds (mas) [31]. This is roughly a factor of 1 000 times better than the previously reported localizations (see Figure 1, left).…”
Section: The Absence Of Compact Persistent Emission Associated With F...mentioning
confidence: 81%
“…We followed up FRB 20201124A within the PRECISE project during different epochs and, we detected 13 and 5 bursts in two of them [30]. By combining the data from all these bursts, we were able to localize FRB 20201124A with a 1-𝜎 uncertainty of 2.7 milliarcseconds (mas) [31]. This is roughly a factor of 1 000 times better than the previously reported localizations (see Figure 1, left).…”
Section: The Absence Of Compact Persistent Emission Associated With F...mentioning
confidence: 81%
“…Another active repeater FRB 20201124A (Lanman et al 2021;Kumar et al 2021;Nimmo et al 2021;Hilmarsson et al 2021) is found in a Milky-Way-sized, metal-rich, barred-spiral host galaxy at z = 0.098 (Xu et al 2021;Fong et al 2021;Ravi et al 2021;Piro et al 2021). This repeater indicates a significant, irregular, variation of the Faraday rotation over 36 days.…”
Section: Introductionmentioning
confidence: 92%
“…FRB20201124A is a repeater with DM ∼ 410 pc cm (Xu et al 2021), uGMRT (Wharton et al 2021) and VLA (Law et al 2021) and further refined, with a milliarcsecond precision, by the EVN (Nimmo et al 2021b). It was localised in a nearby (𝑧 ∼ 0.098) (Fong et al 2021) galaxy with a high star formation rate which suggests a new-born magnetar as the most likely progenitor (Piro et al 2021).…”
Section: Frb20201124amentioning
confidence: 99%